Design of a differential protection scheme for a 345 kV transmission line using SEL 311L relays - Subrahmanyam, Tarangini Karoor (Kansas State University, 2014)
Transmission networks are an important part of an electric power system. They help transfer power from the point of generation (power plants) to the substation. In order to minimize losses during power transfer, the lines are operated at high voltages. The high voltage lines not only have a high power transmission capacity, but they are also prone to faults of larger magnitudes. Thus the occurrence of such faults results in a need for the faults to be cleared quickly in order to limit damage caused to the system. Hence, relays are installed at the Buses to provide protection to the lines. Transmission lines in a power system are most commonly protected by distance relays that use directional comparison schemes. However, due to the simplicity of line differential schemes, there has been an increase in the use of differential relays for complex networks. Moreover, since the relays require only current as the operating parameter, their settings can be determined easily. This report discusses the design of a line current differential protection scheme for a transmission line using SEL 311L relays. The relay settings have been determined and then tested for seven fault scenarios, three internal fault points and four external fault points. To set and test the relays, AcSELerator Quickset, SEL 5030 and PowerWorld programs have been used. Real life power system is simulated with the help of SEL AMS (Adaptive Multichannel Source) that acts as the source to provide the required data to the relays. The relays trip and open the breaker contacts for an internal fault. During an external fault, the relays do not trip and the breaker contacts remain closed. The response of the relays in case of communication failures has been discussed.
Keywords: Power; Transmission line; SEL relays; Differential protection; Electrical Engineering (0544); Engineering (0537)